ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2017 (Studi Kasus pada PT. Xl Axiata Tbk dan PT. Indosat Tbk) - Afriadin Afriadin; Jeni Susyanti; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThe company was established as a business that aims to obtain maximum profits and will also affect the economy of a country. So that requires companies to have good financial performance. company financial performance can be seen from the financial statements in the previous period and will be a reflection of the improvement in the next period by analyzing the company's financial ratios. This study aims to analyze the financial performance of PT. XL Axiata Tbk with PT. Indosat Tbk. 2014-2017 period in terms of financial ratios, namely: Analysis of Liquidity Ratios, Solvability Ratios, Activity Ratios and Profitability Ratios and To analyze the comparison of Liquidity ratios, Solvability Ratios, Activity Ratios and Profitability Ratios between PT. XL Axiata Tbk with PT. Indosat Tbk. 2014-2017 period. The method used in this study is quantitative data in the form of annual financial statements calculated using liquidity ratio analysis, namely the current ratio, quick ratio, solvability ratio, namely total debt to asset ratio, total debt to equity ratio, activity ratio ie total asset turn over, profitability ratio namely return on investment and return on equity. The analysis tool used is an independent t test. From the calculation results based on value Based on liquidity ratios, profit is limited to PT. Indosat Tbk. has a better ratio than PT. XL Axiata Tbk. while the activity ratio of PT. XL Axiata Tbk has a higher ratio. For the solvability ratio of PT. Xl Axiata Tbk has a higher ratio in the variable debt to Asset ratio (DAR) while in the variable debt to equty ratio (DER) PT. Indosat Tbk has a better value In the independent t test, it was found that there were significant differences between PT. XL Axiata Tbk. and PT. Indosat Tbk based on activity ratios, solvability ratios on debt to asset ratios, and profitability ratios in the return on equity variable, while on liquidity ratios, solvability ratios on the debt to equity ratio, and profitability ratios in the return on investment variable there are no differences that significant in both companies. Keywords: comparative analysis, financial performance, financial ratio